The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/prilozi-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease – pediatric risk factors

Abstract: The knowledge about the progression of chronic kidney disease is an important issue for every pediatric nephrologist and pediatrician in order to implement appropriate measures to prevent wasting of renal function and the final consequence - end stage renal disease with the need for the dialysis and transplantation. Therefore it is important to know, treat or ameliorate the standard risk factors such as hypertension, proteinuria, anemia, hyperparathyroidism etc. In this review devoted to the World Kidney Day 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…As pointed out by Ahn et al, it is very important as the number of children with CKD is constantly increasing and they develop multiple comorbid conditions such as growth failure, developmental and neurocognitive defects, and impaired cardiovascular health [ 16 ]. Moreover, the number of risk factors, such as prematurity or low birth weight, obesity, smoking, hyperuricemia, acute kidney injury, contributing to the development of CKD is increasing [ 16 , 17 ]. The prevalence of pediatric CRF in Lithuania was analyzed for the first time in 1997 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Ahn et al, it is very important as the number of children with CKD is constantly increasing and they develop multiple comorbid conditions such as growth failure, developmental and neurocognitive defects, and impaired cardiovascular health [ 16 ]. Moreover, the number of risk factors, such as prematurity or low birth weight, obesity, smoking, hyperuricemia, acute kidney injury, contributing to the development of CKD is increasing [ 16 , 17 ]. The prevalence of pediatric CRF in Lithuania was analyzed for the first time in 1997 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis of uric acid is maintained primarily by hepatic metabolism, and the excretion of redundant uric acid occurs through urine and faeces. 1 The physiological saturation threshold of uric acid to monosodium urate (MSU) is 6.8 mg dl −1 (360 μmol L −1 ), and serum urate levels that exceed this limit are indicators of hyperuricemia. 2 Except for acute gout, hyperuricemia shows no symptoms and is a stable condition termed asymptomatic hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a major risk factor in progression of chronic kidney diseases (20) in the pediatric population (21). A major component of cigarette smoke is NIC (2), which connects smoking to renal injury via inducing oxidative stress (3).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of active smoking in renal risk is recognized, the role of second-hand smoke is overlooked (21). Experimental studies showed that rats exposed to passive smoking not only develop renal oxidative stress and fibrosis (24) but are also more sensitive to oxidative stress and related fibrosis caused by other environmental pollutants (24).…”
Section: Discussionmentioning
confidence: 99%